'Let's see who's being creative out there': Lessons from the 'Creative Citizens' programme in Northern Ireland. (1st April 2017) - Durrer, Victoria
Policy critiques indicate that strategies aimed at fostering participation in publicly funded arts have focused too heavily on individuals' capacity for engagement, rather than on the capacity of the sector to engage individuals. Programmes like 'Creative People and Places' (CPP) see this capacity as shared, community networks, ideas, infrastructure and skills. Through analysis of one local council's Arts Development Service, specifically Mid and East Antrim Borough Council (MEABC) in Northern Ireland (NI), this article brings the role and position of local government work to light within this broader understanding of capacity as a community-wide phenomenon. Through focusing on the assumptions, operations and experiences regarding cultural participation held by MEABC's arts staff, the article enhances the learning about community capacity more formally underway in the CPP projects and supports the notion that capacity building is a multi-directional process. In taking a new approach to programme delivery, the team's assumptions and beliefs about cultural participation and infrastructure have been challenged. This change in perception has impacted the development of their practice to promote and develop arts and cultural participation in their locality. The study has implications for what more democratic practices of participation might mean to the strategic decision-making processes of local cultural policy development and governance. As a result, the article advocates for more and deeper consideration of local government as a key actor in the arts and cultural sector and cultural policy-making.